(untitled) (American Journal of Islam and Society, 2025)
Musab Younis, originally from Manchester, completed his MPhil (2012) and DPhil (2017) in International Relations at Oxford, under Andrew Hurrell,1 where he later served as a College Lecturer in Politics at St Peter’s College. From 2018 to 2024, he was a Lecturer and then Senior Lecturer in Politics at Queen Mary University of London before returning to Oxford in 2024 as an Associate Professor of Political Theory. His research focuses on international political thought, theories of race and racism, empire, and anticolonialism during the late nineteenth and twentieth centuries, connecting historical perspectives on empire with contemporary political theory. His work explores anticolonial political thought, especially Black and African anticolonialism, the history of race and racism, and issues of space, scale, and globality such as the North vs. South division of the world. He is currently working on a monograph about the intellectual history of global inequality, tentatively entitled The Pillage of Distant Worlds, while also simultaneously pursuing projects on the intimate politics of imperialism, demographic catastrophism, settler colonialism, and the concepts of speed and self in anticolonial thought. He has published academically on anticolonialism, race, nationalisms, transnationalism, internationalisms, labor, etc. Moreover, Musab Younis has published articles in the London Review of Books, the Guardian, Prospect, Baffler, and n+1, among other outlets.